2003
DOI: 10.1111/1467-6486.00397
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Incentive Plans, Executive Pay and UK Company Performance*

Abstract:  In agency theory, the remuneration packages of executive directors in large companies are seen as an attempt to give them a pattern of rewards that aligns their interests more closely with shareholders as a whole. The sensitivity of total executive rewards to share price performance has become the conventional yardstick for judgements concerning whether reward packages do indeed serve shareholders' interests or executives themselves.Long-term incentive plans (LTIPs) introduced in the UK from 1995 have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(65 citation statements)
references
References 38 publications
5
59
1
Order By: Relevance
“…More evidence is required, but the conjecture is consistent with the phenomenon of executive pay inflation during the period that long-term incentives have come to comprise an ever greater proportion of total compensation. It is also, as we have already pointed out, consistent with the arguments based on rational choice theory and deductive logic advanced by Lambert, Larcker and Verrechia (1991), Meulbroek (2001), Hall and Murphy (2002) and Buck, Bruce, Main and Udueni (2003).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…More evidence is required, but the conjecture is consistent with the phenomenon of executive pay inflation during the period that long-term incentives have come to comprise an ever greater proportion of total compensation. It is also, as we have already pointed out, consistent with the arguments based on rational choice theory and deductive logic advanced by Lambert, Larcker and Verrechia (1991), Meulbroek (2001), Hall and Murphy (2002) and Buck, Bruce, Main and Udueni (2003).…”
Section: Discussionsupporting
confidence: 91%
“…Although based on a fundamentally different logic, this is consistent with previous research by Lambert, Larcker and Verrechia (1991), Meulbroek (2001), Hall and Murphy (2002) and Buck, Bruce, Main and Udueni (2003), on which we comment further in the theory and discussion sections. The paper proceeds as follows.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Pass (2003) found that most LTIPs were undemanding and rewarded average instead of outstanding performance. Buck et al (2003) concluded that LTIPs are generally associated with reductions in the sensitivity of the relationship between executives' total rewards and shareholder returns and thus questioned their effectiveness. Walker (2010) also concluded that there is an inadequate relationship between executive compensation and long-term company performance.…”
Section: Literature Reviewmentioning
confidence: 99%